In vitro spermatogenesis in two‐dimensionally spread mouse testis tissues. (13th August 2019) - Komeya, Mitsuru; Yamanaka, Hiroyuki; Sanjo, Hiroyuki; Yao, Masahiro; Nakamura, Hiroko; Kimura, Hiroshi; Fujii, Teruo; Sato, Takuya; Ogawa, Takehiko
Abstract: Purpose: Mouse in vitro spermatogenesis is possible with classical organ culture methods, by placing the testis tissue at the interphase between culture medium and air. In this condition, however, a tissue piece tends to round up to be compact, whose central region suffers from shortage of nutrients and oxygen. In this study, the authors improved the culture condition by spreading each tissue thin and flat, by which they were able to get better access to the oxygen and nutrients. Methods: Immature mouse testis tissues placed on agarose gel block were forced to spread flat by covering with a polydimethylsiloxane (PDMS) ceiling chip (PC chip). They were then cultured for weeks and evaluated by the transgene expression of Acr‐Gfp, which reflects the progression of spermatogenesis. Results: Testis tissues covered with PC chip initiated and maintained spermatogenesis in its wider region than those without PC chip covering. Flow cytometric analysis demonstrated that the PC method yielded more numerous meiotic germ cells than those without PC. Immunohistochemical examination confirmed the authentic histological figure of spermatogenesis from spermatogonia up to round or elongating spermatids. Conclusions: The PC chip method is simple and effective to improve the efficiency of in vitro spermatogenesis in the organ culture system.